2021
DOI: 10.3389/fonc.2020.619803
|View full text |Cite
|
Sign up to set email alerts
|

Deep Convolutional Neural Network-Based Lymph Node Metastasis Prediction for Colon Cancer Using Histopathological Images

Abstract: BackgroundHuman evaluation of pathological slides cannot accurately predict lymph node metastasis (LNM), although accurate prediction is essential to determine treatment and follow-up strategies for colon cancer. We aimed to develop accurate histopathological features for LNM in colon cancer.MethodsWe developed a deep convolutional neural network model to distinguish the cancer tissue component of colon cancer using data from the tissue bank of the National Center for Tumor Diseases and the pathology archive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Artificial neural network (ANN) is a mathematical or computational model that uses structures similar to synaptic connections in the brain to process information [ 9 ]. ANN models have been applied to risk assessment of many diseases, including colon cancer, lung cancer, hepatocellular carcinoma, meningioma, and so on and have shown reliable and accurate performance in disease prediction and evaluation [ 10 13 ]. However, no studies have been reported on predicting prostate cancer risk based on ANN models.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial neural network (ANN) is a mathematical or computational model that uses structures similar to synaptic connections in the brain to process information [ 9 ]. ANN models have been applied to risk assessment of many diseases, including colon cancer, lung cancer, hepatocellular carcinoma, meningioma, and so on and have shown reliable and accurate performance in disease prediction and evaluation [ 10 13 ]. However, no studies have been reported on predicting prostate cancer risk based on ANN models.…”
Section: Introductionmentioning
confidence: 99%
“…The images are representative of stages 1 through 3 of cancer, which means that the cancer has not yet spread to other organs. [32] The polyps are the growths that can be become the tumors, some studies directly analyze them, since there is a chance, it does not become cancerous. Patel et al in their study trained a number of six CNN on their dataset.…”
Section: B Ai Diagnosis For Colorectal Cancermentioning
confidence: 99%
“…Machine learning approaches started to improve medical care and biomedical research in recent years. It has been used in fields such as radiology, telehealth, clinical care, and even stem cell biology [20,[31][32][33].…”
Section: Microscopic Preservation Of Cardiac Ecmmentioning
confidence: 99%